The Seasonal Distribution of a Highly Commercial Fish Is Related to Ontogenetic Changes in Its Feeding Strategy - Lloret-Lloret, Elena; Navarro, Joan; Giménez, Joan; López, Nieves; Albo-Puigserver, Marta; Pennino, Maria Grazia; Coll, Marta (Frontiers in Marine Science, 2020)
Improving the knowledge on the biology, ecology and distribution of marine resources exploited by fisheries is necessary to achieve population recovery and sustainable fisheries management. European hake (Merluccius merluccius) is one of the most important target species in the Mediterranean Sea and is largely overexploited by industrial fisheries. Here, we used two methodological approaches to further investigate the seasonal variation in the spatial distribution of European hake considering ontogenetic changes and trophic ecology in the western Mediterranean Sea. Our main aim was to explore if spatial changes in hake distribution were related to trophic behaviour, in addition to key environmental factors. We employed a hierarchical Bayesian species distribution modelling approach (B-SDM), using spatial data from two oceanographic surveys conducted during winter and summer. We analysed how the environmental variables, together with abundance and mean weight distribution of the main preys identified for European hake, affected the seasonal distribution of the species. Results revealed clear differences in the distribution of the European hake between seasons, which were indeed partially correlated to the distribution of their main preys, in addition to the environment. Stable isotope values and Bayesian isotopic mixing models (MixSIAR) revealed substantial seasonal and ontogenetic differences in trophic habits of European hake, partly matching the spatial distribution results. These findings could have implications for a future seasonal-based adaptive fisheries management, as local depletion of prey, or variation in size and condition may affect European hake presence in this area. Moreover, this study illustrates how the sequential application of methodologies provides a more holistic understanding of species seasonality, which is essential to understand the phenological processes of exploited species and their potential shifts due to environmental changes.